Algorithmic Mimesis: Translation, Technology, Resistance - Slessor, Stephen; Voyer, Anne (TTR)

(untitled) (Association canadienne de traductologie, 2016)
Translation technologies often figure translation as a simple process of linguistic transfer from one code to another or as a question of selecting the correct matching segments from a database. The prominence of such technologies in the digital age has thus renewed discussions of fidelity and equivalence for translators. The critical attention given to broader cultural and textual contexts that came into focus with the cultural turn seems at risk of disappearing into cyberspace. However, the ongoing proliferation of textual production and reproduction also foregrounds the possibilities of variability and difference in repetition. Using the foibles of technology as catalysts for their own creative ventures, digital-age artists such as Urayoán Noel and Malinda Kathleen Reese channel deficiencies productively in their art, revealing the unsuspected potentials of digital technologies. Such a view of translation as creation challenges the commonplace notion that translation is a scientific act of “carrying across,” a purely semantic transfer that results in the (illusion of) identicality of source and target. Echoing Lévi-Strauss’s notion of “bricolage”—the means by which people retrieve and recombine cultural materials to create new content—Reese and Noel shatter the semantic shackles of identicality by using technology to retrieve and transform the material scraps of language and culture. Their art helps us reconceptualize translation and go beyond fixed notions of what a translation should be or do in terms of fidelity and equivalence. Their playful misuse of machine translation and voice-recognition software allows for a critical analysis of the tension between the universal and the particular as it relates to the act of translation, and does so in a way that uses formal experimentation and humour to resist traditional power dynamics.